97.1k views
4 votes
Solve the equations.
6b–(3–4b)=–8

User Shawn Yap
by
4.9k points

1 Answer

6 votes

Answer:

b = -1/2

Explanation:

6b - (3 - 4b) = -8

Distribute the negative sign on the left side. It is as if -1 is written there. Be careful with the negative sign. It changes all signs inside the parentheses.

6b - 3 + 4b = -8

Combine like terms on the left side.

10b - 3 = -8

Add 3 to both sides.

10b = -5

Divide both sides by 10.

b = -5/10

Reduce the fraction.

b = -1/2

User Chanukya
by
4.5k points